PENGARUH PRODUCT MARKET COMPETITION TERHADAP FIRM VALUE MELALUI EXECUTIVE INCENTIVE SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR NONMIGAS YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Gherallzic Patrickara Sidupa; Devie Devie Devie (Business Accounting Review, 2017)
This study aimed to examine the direct and significant affect of product market competition to executive incentive, product market competition to firm value, and executive incentive to firm value in nonmigas manufacturing companies in Indonesian Stock Exchange. This study also examine the indirect and significant relationship of product market competition to firm value through executive incentive as intervening variable in nonmigas manufacturing companies in Indonesian Stock Exchange. This study used a quantitative approach, and the data were obtained from financial reporting of companies listed in Indonesian Stock Exchange between 2011-2015 and processed by using smartPLS software. This study showed that there was positive and significant relationship of product market competition to firm value, and negative and significant product market competition to executive incentive; and executive incentive to firm value. But, executive incentive was inadequate to become as intervening variable between product market competition and firm value because the direct relationship between product market competition and firm value gave greater affect than if it was through executive incentive.